Stakeholder Influence on Adoption of Circular Economy Principles: Measuring Implications for Satisfaction and Green Legitimacy - Baah, C.; Afum, E.; Agyabeng-Mensah, Y.; Agyeman, D.O. (Springer Link, 2022)
Stakeholder roles in the adoption of circular economy concepts and corresponding impacts on firms have been crucial for academics and practitioners. However, substantial research gaps exist in relation to the specific influence of organizational, regulatory and community stakeholder groups on the adoption of circular economy principles and how these affect internal and external stakeholder satisfactions and green legitimacy in the context of an emerging economy. Drawing on the stakeholder and institutional theories, stakeholder pressures, adoption of circular economy principles, stakeholder satisfaction and green legitimacy were explored. Using a quantitative approach, the findings showed that regulatory stakeholders have the most influence on adoption of circular economy principles, followed by organizational and community stakeholders. In particular, adoption of circular economy principles robustly influenced external stakeholder satisfaction and green legitimacy while moderately influencing internal stakeholder satisfaction. These findings serve as a guide for policy making, management decision making and future research.
Research Article
Keywords: Stakeholder influence; Circular economy principles; Internal and external stakeholder satisfactions; Green legitimacy; PLS-SEM